Revolution or Resignation? The Satirical Purpose of Stephen Leacock's Arcadian Adventures with the Idle Rich. - Kiedrowski, Jonas (American Review of Canadian Studies, 2020)
Stephen Leacock's Arcadian Adventures with the Idle Rich is a damning satire of bourgeois power in a liberal democracy. Its critique is so pointed that the book has been approved for publication by at least one socialist regime. However, a close examination of Arcadian Adventures reveals very little that is revolutionary. Revolutions hinge upon implementing a new ideology. Because ideology has three components—critique, ideal, and agency—and because satire, as a critique, emphasizes only one of ideology's three components, Adventures lacks the ideological roadmap to guide a revolution. The book may share with revolutionary leftists a critique of the bourgeoisie, but it also works in counter-revolutionary ways by pillorying and obfuscating the leftist revolutionary movements intent on overthrowing the bourgeoisie. When considered this way, Arcadian Adventures with the Idle Rich is not so much revolutionary as it is a red tory's cautionary tale, meant to help preserve western liberal democracy.